2009
DOI: 10.1166/jnn.2009.j086
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Responsive Organogels Prepared Through Surface-Initiated Atom Transfer Radical Polymerization on Iron Nanoparticles

Abstract: Iron nanoparticles (Fe(np)) with average diameter 50 nm have been synthesized by addition of NaBH4 to FeCl3 solution then radical initiator, (11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane (1) has been immobilized on to Fe(np). Surface-initiated atom transfer radical polymerization (SI-ATRP) of different monomers such as styrene, methyl methacrylate, methacrylonitrile and N-vinylimidazol have been carried out from initiator-grafted Fe(np) and the amount of grafted polymers was determined by thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…It should be noted here that SEM investigation of these Sil-PNVP particles revealed the presence of insoluble, most likely cross-linked domains precluding the separation of the hybrid particles from each other and the formation of a fine suspension (Figure S6). Most probably, the relatively high grafting density of 2c , the lack of solvent and the noncontrolled feature of the polymerization resulted in high concentration of propagating radicals that might undergo radical termination reactions giving nonsoluble cross-linked network …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted here that SEM investigation of these Sil-PNVP particles revealed the presence of insoluble, most likely cross-linked domains precluding the separation of the hybrid particles from each other and the formation of a fine suspension (Figure S6). Most probably, the relatively high grafting density of 2c , the lack of solvent and the noncontrolled feature of the polymerization resulted in high concentration of propagating radicals that might undergo radical termination reactions giving nonsoluble cross-linked network …”
Section: Resultsmentioning
confidence: 99%
“…Most probably, the relatively high grafting density of 2c, the lack of solvent and the noncontrolled feature of the polymerization resulted in high concentration of propagating radicals that might undergo radical termination reactions giving nonsoluble cross-linked network. 32 Further characterization of polymer-grafted particles was performed using infrared spectroscopy (Figure 4). The DRIFT spectrum of Sil-PNVP 2c (d) is the superposition of the spectra of the three components: silica gel (a), initiatorgrafted silica (b), and PNVP (c).…”
Section: Synthesis Ofmentioning
confidence: 99%
“…During the last several years, this reversibility has made LMOG gels very attractive materials for a large number of applications [3][4][5] in the cosmetics, 6 food 7,8 and pharmaceutical 9,10 industries. Obviously, for these applications, the LMOGs must be non-toxic.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocomposite hydrogel (NC gel) was first reported by Haraguchi and Takehisa; this hybrid gel was prepared by in situ free radical polymerization of monomers from the initiator absorbed on the sheet-like nanoclay by ionic interactions. 6 Huang et al 7 and Czaun et al 8 reported that a hybrid hydrogel could be formed by the termination of grafting polymer chains growing from the surfaces of the particles. More recently, Wang et al reported that nanoparticles coated with a specific polymer with a dendritic structure at both its terminals underwent aggregation by electrostatic interactions, thereby inducing gel formation.…”
mentioning
confidence: 99%